Effect of the Y2O3 additive concentration on the properties of a silicon nitride ceramic substrate - Liu, Wei; Tong, Wenxin; He, Rongxuan; Wu, Haidong; Wu, Shanghua (Ceramics international, 2016)
Silicon nitride (Si3N4) ceramics offer excellent thermal, mechanical and dielectric properties, which make Si3N4 a good candidate material for an application as electronic packaging material. For an application as a heat dissipation substrate, most studies focused on achieving a high thermal conductivity through long-time heat preservation and different kinds of heat treatments. Very few studies also considered the mechanical and dielectric properties. In addition, there have not been systematic researches about influence of additives concentration and type on the combination properties of Si3N4. Therefore, in this study, Si3N4 ceramic samples were prepared via hot pressing at 1800°C with a relatively short heat preservation step (2h), with different amounts of Y2O3 added as sintering additive. The effect of the initial concentration of the rare earth oxide on the chemical composition, microstructure, thermal conductivity, as well as the mechanical and dielectric properties of the Si3N4 ceramic samples was systematically studied.